Analysis of Comorbidity and Its Association with Disease Severity and Mortality Rate in Hospitalized COVID-19 Patients - Anthony Christanto; Aditya Sri Listyoko; Ngakan Putu Parsama Putra (Jurnal Respirologi Indonesia, 2022)
Background: Comorbidity is a major factor in determining the outcome of COVID-19. However, existing studies regarding comorbidities and the disease severity and mortality of COVID-19 are mostly based on studies in the whole community, and not on those admitted to hospitals. This study aims to determine the demographic profile of comorbidities among COVID-19 patients hospitalized in tertiary care referral hospitals and its association with disease severity and mortality. Methods: We analyzed the data from 60 laboratory-confirmed patients in our hospital in Malang City, East Java, Indonesia from March 12th, 2020 to June 5th, 2020. We describe the demographic profile of the patients and perform statistical analysis to determine its relationship to disease severity and mortality. Results: The majority of the study samples (66.7%) were categorized as having a severe disease. Thirty-seven samples (61.7%) had at least one comorbidity. The mortality rate among the study population is 30.0%, and 37.8% among those with comorbidities. The most prevalent comorbidity was hypertension (40.0%), followed by heart failure (35.0%) and diabetes (25.0%). There is a statistically significant relationship between the presence of comorbidities and disease severity and between disease severity and mortality (p<0.05). Diabetes was the only comorbidity with a significant relationship towards mortality in our study (p<0.05, OR 4.0 95% CI 1.16-13.74). Conclusion: Comorbidities are associated with worse disease severity and death in hospitalized COVID-19 patients.